THE ISSUE OF MEASUREMENT IN THE SERIES OF "YUSUF AND ZULAIKHO" SERIES - Rakhmonova Shakhnoza Mukhitdinovna (Journals Park Publishing, 2024)
This article analyzes the issue of measurement in the epics of the "Yusuf and Zulayho" series. To read them expressively, features of meter, measurement possibilities, rhyme system were studied. At the same time, there is a reaction to the opinions in literature.
Keywords: aruz, meter, epic, mutakarib bahri, khazaj bahri, sari' bahri.